Heavy metal accumulation in the liver of Antarctic minke whale (Balaenoptera acutorostrata) (extended abstract) - Honda,Katsuhisa; Yamamoto,Yoshiyuki; Tatsukawa,Ryo (1986)
P(論文) departmental bulletin paper